(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
Trichoderma species have been registered as species with important plant growth promoting potential and antagonistic effect against various phytopathogens. Trichoderma isolates originating from different soil types from the Vojvodina region (Serbia) were screened using dual culture test for their antagonistic effect against the pathogen Sclerotinia sclerotiorum. All tested isolates had high radial growth inhibition (RGI) factors of the pathogen and high colonization percentage. Growth promoting activity of Trichoderma isolates on soybean seeds was tested under glasshouse conditions. Soybean seeds were coated with suspensions of different Trichoderma isolates and seed germination percentage, root and shoot length were measured. According to data analysed in Statistica 10, using Duncan’s test, there were no significant effects on shoot length among the tested isolates, compared to the control. The four tested Trichoderma isolates showed significant positive effects on germination, root length and vigour index, while two isolates exhibited no significant effect on any of the measured parameters.